Screen Printed Electromechanical Micro-total Analysis System (μtas) for Sensitive and Rapid Detection of Infectious Diseases. (2017) - Nordin, Anis Nurashikin; Zainuddin, Ahmad Anwar; Rahim, Rosminazuin Ab; Voiculescu, Ioana; Mak, Wing Cheung
Abstract: The main objective of this article is to demonstrate by performing simulation measurements of biosensor that can detect the presence of pathogens through simultaneous mass and impedance techniques. This biosensor merges two biosensing techniques namely resonant frequency measurements and electrochemical impedance spectroscopy (EIS) on a single biosensor. Parallel measurements provide better sensitivities, have higher diagnostics accuracy and reduce the risk of false positives. Low cost, high resolution screen printing technology was used to fabricate the microelectromechanical array of μTAS on flexible piezoelectric substrates. The basic biosensor framework includes a substrate that highly sensitive sensor like thickness shear mode and immunosensor can be fabricated using quartz crystal lattice that integrated with electrochemical sensor [1]. The quartz crystal microbalance is a label free technique, which minimizes interference with the interaction being studied. A piezoelectric device is portable, simple and cost effective, and is suitable for real-time monitoring of biospecific interactions such as antigen-antibody, receptor ligand, and enzymes-substrate interactions with high sensitivity and specificity. For instance, the biological mixtures such as antibodies are capable of binding to terminal active functional groups ( i.e., COOH, OH and NH2 ) of self-assembled monolayers (SAM) and immunocapture antigens such as glycoproptien or other targets[2]. The QCM can consequently detect mass changes due to these molecular interactions on the surface of the QCM. The top and bottom circular excitation electrodes with 150um diameter were modeled as gold (Au) films of 16 μm thickness. A sinusoidal voltage with amplitude of 5 mV was applied across the quartz crystal. Figure 1 shows the principle of integrated biosensors which gold electrodes were printed on both sides of a thin 500um quartz layer to form the quartz crystal microbalance (QCM)-impedance device. The silver (Ag) semicircular counter electrode was modeled around the top working electrode on the same area of the quartz crystal for performing the electrochemical impedance spectroscopy (EIS) experiments for detection of bacteria (E-Coli) and the results were compared to quartz crystal microbalance measurements. Furthermore, the use of gold surface can be incorporated into the transducer compatible with the biological samples such as use of highly specific monoclonal antibodies, and incorporation of amplification step to maximize the signal detection. In general, the quartz crystal is traditionally considered to be a mass sensitive sensor that produces response which it changes its resonance frequency to different thin film samples or liquids in contact with it surface. For a straight relationship between a thin film mass of the order of nanograms, the quartz crystal response will be of of the order of Hertz according to Eq. 1, Sauerbrey Equation [3]. ρ q and μ q are the specific density and the shear modulus in quartz, respectively. ϝ0 is the fundamental resonance frequency in quartz, related to its thickness, n q . Δm is the thin film mass deposited A, is the piezoelectrically active crystal area and n is the overtone number. Based on Eq. 1, it can be found that if the density of QCM changes, the resonant frequency of the device also changes, making the QCM suitable for monitoring changes in mass. In contact with liquids, the crystal is capable of giving information about the density-viscosity product ( √ρn ) of the fluid by changing its resonance frequency and quality Q-factor according with Eq.3, Kanazawa equation[3]: Where ρ L and η L are the density and viscosity in fluid respectively. Whilst, Eq. 4 indicates the decay characteristic length (δ) as linear relationship to the ratio viscosity to density of the liquid and inversely proportional the angular frequency (ω). Prior to device fabrication, 3D electric field analysis, resonant frequency simulations and thickness shear deformation were performed using automatic meshers by COMSOL Multiphysics. The resonator was modeled in three dimensions (3D), as an AT-cut quartz substrate of 500 μm thickness. The eigenfrequency analysis was performed to produce the quartz surface displacement and thickness shear deformation. The frequency domain analysis was conducted to obtain the resonant frequency of the resonator. Here we have tested the performance of the application of biosensors mainly in the detection of E-coli bacteria using QCM-impedance device using Escherichia coli cells as model of detection. Both frequency and impedance measurements were successfully obtained using cells both in media and in distilled water. We believe than this work offers a promising solution for the next generation of healthcare devices where high accuracy results are provided by low cost sensors.